A rational approach to e-cigarettes: challenging ERS policy on tobacco harm reduction. Issue 5 (7th May 2020) - Britton, John; George, Jacob; Bauld, Linda; Agrawal, Sanjay; Moxham, John; Arnott, Deborah; McNeill, Ann; Hopkinson, Nicholas S.
The respiratory community is united in its desire to reduce and eliminate the harm caused by tobacco smoking, which is at present on course to kill one billion people in the 21st century. The stated policy of the European Respiratory Society is to strive "constantly to promote strong and evidence-based policies to reduce the burden of tobacco related diseases". In our view, the recent ERS Tobacco Control Committee statement on tobacco harm reduction [1], though well-intentioned, appears to be based on a number of false premises and draws its conclusions from a partial account of available data. It also presents a false dichotomy between the provision of "conventional" tobacco control and harm reduction approaches. We therefore respond, in turn, to the seven arguments presented against the adoption of harm reduction in the Committee's statement. The current ERS Tobacco Control Committee statement rejecting harm reduction does not reflect the state of evidence around the effectiveness and safety of e-cigarettes and may be harmful if implemented http://bit.ly/39ix5iO